2020
DOI: 10.1186/s12913-020-05245-y
|View full text |Cite
|
Sign up to set email alerts
|

Community pharmacy teams’ experiences of general practice-based pharmacists: an exploratory qualitative study

Abstract: Background In England, since 2015, there has been a formal drive to integrate pharmacists into general practice as a new healthcare service. Research efforts have offered insights into how general practice-based professionals and patients view the service, however, they took no account of community pharmacy teams’ opinions. There have been anecdotal statements about opposition from community pharmacies to the service, due to fears of losing business. The aim of the current study was to identify the experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…A recent qualitative study indicated that community pharmacists were aware of pharmacists’ presence in general practice but were uncertain about details such as employment models, roles and responsibilities. This highlights that there is a need to inform community pharmacists about PBPs’ scope of practice and to introduce formal regular meetings between community pharmacy and general practice staff [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent qualitative study indicated that community pharmacists were aware of pharmacists’ presence in general practice but were uncertain about details such as employment models, roles and responsibilities. This highlights that there is a need to inform community pharmacists about PBPs’ scope of practice and to introduce formal regular meetings between community pharmacy and general practice staff [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this review, it was shown that a key priority of the general practice pharmacist was to act as a conduit between community pharmacy, hospital pharmacy, and the general practice [ 57 , 58 ]. Community pharmacists appeared less enthusiastic towards pharmacists working in general practice according to one Australian article [ 54 ], while international studies have reported mixed views on the relationship between community pharmacists and general practice pharmacists: this includes a good rapport, and significant tensions stemming from professional hierarchy and competing business-related interests [ 9 , 74 , 75 ]. However, there is a knowledge gap in examining the impact of liaison between community pharmacists and general practice-based pharmacists, mainly around HMRs, smoking cessation, and lifestyle advice [ 54 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Poor relationships and infrequent collaborative efforts between community pharmacists and GPs are common issues encountered in primary care [ 34 ]. One possible approach to improving collaboration is thought to be via GP pharmacists, who could assist with building rapport between settings, unifying and improving patient care [ 35 ]. Furthermore, stock shortages have been an increasingly encountered problem for patients due to multiple supply chain disruptions [ 36 , 37 ] with a particularly difficult period arising in 2019 [ 37 – 39 ] from when this feedback data was extracted from CareOpinion.…”
Section: Discussionmentioning
confidence: 99%